A rare cause of recurrent extubation failure in an infant - Jogender Kumar; Arushi Yadav (Hygeia Press di Corridori Marinella, 2018)
Despite multiple chest radiographs showing elevated hemidiaphragm, untrained eyes failed to notice it. "The eyes do not see what the mind does not know" is a saying well demonstrated by our patient who had multiple extubation failures secondary to recurrent lung collapse, that too on the same side. On reviewing all radiographs simultaneously, we suspected left side diaphragmatic palsy, which was later confirmed on ultrasonography. In spite of clear demonstration of elevated hemidiaphragm on multiple serial X-rays, diagnosis of diaphragmatic palsy was missed leading to delay in diagnosis, unnecessary antibiotics, and prolonged ventilation. There was a spontaneous recovery of the function of the affected side of the diaphragm, and he could be successfully extubated and subsequently discharged.